The Potential Impact of Dietary Fiber Supplementation on Hemoglobin and Reticulocyte Hemoglobin Equivalent (RET-He) Levels in Pregnant Women with Anemia Receiving Oral Iron Therapy in Indonesia - Afifah A; Zuhairini Y; Ariyanto EF; Ghozali M; Fatimah SN; Pramatirta AY (Journal of Multidisciplinary Healthcare)
Adilah Afifah,1 Yenni Zuhairini,2 Eko Fuji Ariyanto,3 Mohammad Ghozali,3 Siti Nur Fatimah,2 Akhmad Yogi Pramatirta4 1Master Program of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, 40161, Indonesia; 2Department of Public Health, Faculty of Medicine, Universitas Padjadjaran, Sumedang, West Java, 45363, Indonesia; 3Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Sumedang, West Java, 45363, Indonesia; 4Department of Obstetrics and Gynecology, Faculty of Medicine, University of Padjadjaran, Dr. Hasan Sadikin General Hospital, Bandung, West Java, 45363, IndonesiaCorrespondence: Yenni Zuhairini, Department of Public Health Sciences, Faculty of Medicine, Universitas Padjadjaran, Jl. Raya Bandung-Sumedang Km.21, Sumedang, West Java, 45363, Indonesia, Email yenni@unpad.ac.idPurpose: Anemia during pregnancy can lead to physical and cognitive impairments, fatigue, and postpartum depression. Dietary fiber, as a prebiotic, supports gut health by producing short-chain fatty acids, which enhance immunity and aid iron absorption. This study investigates the impact of fiber supplementation on hemoglobin and reticulocyte hemoglobin equivalent (RET-He) levels in anemic pregnant women receiving oral iron therapy.Patients and Methods: This study used a quasi-experimental design with a control group. The subjects were anemic pregnant women between 14 and 32 weeks of gestation. Fifteen control subjects received iron tablets and skim milk (placebo), while 25 intervention subjects received iron tablets and a fiber supplement containing 7.2 grams of dietary fiber. Hemoglobin and RET-He levels were measured before and after the intervention with a Sysmex hematology analyzer. The differences in hemoglobin and RET-He changes were analyzed using the independent sample T-test.Results: After 14 days of intervention, the average hemoglobin increase in the intervention group was 0.772± 0.815, compared to 0.167± 0.564 in the control group, with a p-value of 0.016. There was a significant decrease in the intervention group (p=0.018) and the control group (p=0.008) with normal RET-He values. The average change in RET-He values for the normal group with intervention was − 1.44 ± 0.99 and control was − 1.63 ± 1.19 (p=0.715), while for the low group with intervention it was 1.65 ± 3.024 and control was 0.55 ± 2.654 (p=0.402).Conclusion: This study concludes that fiber supplementation for 14 days in pregnant women with anemia can significantly increase hemoglobin levels compared to the control group There was a decrease in RET-He values after the intervention in the normal group and an increase in the low group, although it was not statistically significant.Keywords: anemia in pregnancy, fiber, hemoglobin, iron tablets, RET-He